1986
DOI: 10.1063/1.451692
|View full text |Cite
|
Sign up to set email alerts
|

Reaction rate constant of HO2+O3 measured by detecting HO2 from photofragment fluorescence

Abstract: The rate constant for the reaction HO2+O3→OH+2O2 was investigated in a discharge–flow system at room temperature. HO2 was produced from the reaction sequence Cl+CH3OH→CH2OH+HCl and CH2OH+O2→HO2+CH2O. HO2 was detected by the OH(A–X) fluorescence produced from photodissociative excitation of HO2 at 147 nm. A computer modeling of the reaction kinetics occurring in the flow tube was carried out to confirm that contributions from secondary reactions were negligible at low HO2 concentrations. The rate constant was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Initial experimental and theoretical studies were focused solely on the “naked” reaction, with our group then exploring the influence of one water molecule on the reaction’s mechanism and energetics. The importance of studying the influence of water molecules has two sources. One is related to the fact that there is no conclusive evidence from the publications that the experiments on the HO 2 + O 3 reaction do not have the presence of water.…”
Section: Introductionmentioning
confidence: 99%
“…Initial experimental and theoretical studies were focused solely on the “naked” reaction, with our group then exploring the influence of one water molecule on the reaction’s mechanism and energetics. The importance of studying the influence of water molecules has two sources. One is related to the fact that there is no conclusive evidence from the publications that the experiments on the HO 2 + O 3 reaction do not have the presence of water.…”
Section: Introductionmentioning
confidence: 99%
“…A difficulty with direct measurements of k 1 under pseudo-first-order conditions with respect to HO 2 is the rapid regeneration of HO 2 due to this very cycle. Previous studies have used an OH scavenger or have used isotopic labeling of the HO 2 in order to determine k 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies have been reported for the HO 2 + O 3 reaction . An interesting observation is the positive curvature in the Arrhenius‐type plot of lnk1(T) vs. T −1 at low temperatures, often attributed to the competition of distinct reaction channels.…”
Section: Larger Odd‐hydrogen Radicals: Ho4 and Ho5mentioning
confidence: 99%